Peran UMKM Lokal dalam Pengembangan Produk Tanaman Serei sebagai Bahan Anti Nyamuk dalam Meningkatkan Ekonomi Masyarakat Desa Timbang Jaya - Dwi Khairunnisa; Triana Triana; Maura Faradita; Andini Fadhila Hasibuan; Risyad Fakar Lubis (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
This study aims to analyze the role of local Micro, Small, and Medium Enterprises (MSMEs) in utilizing lemongrass (Cymbopogon citratus) as the main ingredient for mosquito repellent products and its contribution to improving the economy of the community in Timbang Jaya Village. Lemongrass contains essential oils that function as a natural insect repellent, making it a potential raw material for value-added products such as mosquito repellent sprays, aromatherapy candles, and herbal lotions. This research employed a descriptive qualitative method with data collected through interviews, observations, and literature studies. The findings indicate that local MSMEs play a significant role in the production process, product innovation, and marketing of lemongrass-based products. Besides generating additional income, this development also creates new job opportunities and supports the village’s economic independence. However, several challenges remain, including limited capital, lack of processing technology skills, and competition with chemical-based products. The recommended solutions include capacity building through training and mentoring, better access to funding, and strengthening digital marketing strategies. Therefore, the development of mosquito repellent products from lemongrass by MSMEs not only contributes to the community’s economic growth but also provides an environmentally friendly alternative beneficial for public health.